2012
DOI: 10.1534/genetics.112.145714
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term and Short-Term Evolutionary Impacts of Transposable Elements onDrosophila

Abstract: Transposable elements (TEs) are considered to be genomic parasites and their interactions with their hosts have been likened to the coevolution between host and other nongenomic, horizontally transferred pathogens. TE families, however, are vertically inherited as integral segments of the nuclear genome. This transmission strategy has been suggested to weaken the selective benefits of host alleles repressing the transposition of specific TE variants. On the other hand, the elevated rates of TE transposition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 135 publications
2
61
1
Order By: Relevance
“…In the soma, transcripts retain the third intron, producing a truncated, inactive version of the transposase protein; in the germ line, this intron is spliced out, yielding a functional transposase (35). Host genes responsible for alternative splicing of the third intron [P-element somatic inhibitor (Psi), heterogeneous nuclear ribonucleoprotein at 27C (Hrb27C)] are highly conserved between D. melanogaster and D. simulans (36), and so we anticipated that the same pattern of alternative splicing occurs in D. simulans. We therefore analyzed RNA-seq data from the Florida D. simulans flies for evidence of alternative splicing of the third intron (Fig.…”
Section: Significancementioning
confidence: 99%
“…In the soma, transcripts retain the third intron, producing a truncated, inactive version of the transposase protein; in the germ line, this intron is spliced out, yielding a functional transposase (35). Host genes responsible for alternative splicing of the third intron [P-element somatic inhibitor (Psi), heterogeneous nuclear ribonucleoprotein at 27C (Hrb27C)] are highly conserved between D. melanogaster and D. simulans (36), and so we anticipated that the same pattern of alternative splicing occurs in D. simulans. We therefore analyzed RNA-seq data from the Florida D. simulans flies for evidence of alternative splicing of the third intron (Fig.…”
Section: Significancementioning
confidence: 99%
“…This deleterious side effect, in combination with 38 the deleterious effects of TE insertions suggests TE insertions should be rare in euchromatic 39regions (Charlesworth and Langley 1989;Charlesworth et al 1997;Lee and Langley 2010). 40Within this model, TEs will enter a genome and spread rapidly through a burst of 41 unsuppressed transposition (Kofler et al 2012;Lee and Langley 2012). The TE will be silenced 42 via the piRNA system and regulated so long as piRNAs are produced against the TE (Senti and 43 Brennecke 2010;Blumenstiel 2011).…”
mentioning
confidence: 99%
“…Although such rapid phenotypic change could imply strong directional selection, population genetic theory has historically suggested that in sexually reproducing eukaryotes, TE repression is only weakly beneficial (Charlesworth and Langley 1986;Nuzhdin 1999;Lee and Langley 2012). Although repressor alleles confer an advantage by reducing the occurrence of new deleterious TE insertions, recombination and independent assortment rapidly separate repressors from the chromosomes that they have protected from TE-induced mutational load (Charlesworth and Langley 1986).…”
Section: Mutation and Selection In The Rapid Evolution Of Host Represmentioning
confidence: 99%
“…To explore the benefits of repressing hybrid dysgenesis, Lee and Langley (2012) examined the strength of selection on a P cytotype-independent repressor of P-element transposition and hybrid dysgenesis during genome invasion with a deterministic model. They observed a sizable selective advantage for the repressor allele (0.6%) when hybrid dysgenesis was common.…”
Section: Mutation and Selection In The Rapid Evolution Of Host Represmentioning
confidence: 99%